Lexical and Grammatical Aspect in On-line Processing of English Past Tense and Progressive Aspect by Mandarin Speakers - Zeng, Xiaoyan; Chen, Xiaoxiang; Shirai, Yasuhiro (Frontiers in Psychology, 2021)
Previous studies have shown that the grammatical aspect of verb predicates has an effect on tense-aspect sentence processing. However, it remains unclear as to whether the interaction of lexical aspect and grammatical aspect can influence the form-meaning association in the second language (L2) tense-aspect sentence processing, especially for the learners whose native language is grammatically marked differently from their L2. This study conducts a psycholinguistic investigation to highlight how the prototypical and non-prototypical associations predicted in the Aspect Hypothesis and L2 proficiency level influence the processing of English past tense and progressive morphology by Mandarin Chinese learners at two proficiency levels and native English speakers. The results show that the prototypical associations of English tense-aspect categories predicted in the Aspect Hypothesis, such as achievement verbs with past tense and activity verbs with the progressive aspect, can engender shorter reading time than non-prototypical associations for both native speakers and second language learners. There is no significant difference between native speakers and Chinese learners of English in their processing of prototypical items, while significant differences exist in the processing of non-prototypical items. The L2 proficiency level does not have an effect on the processing of prototypes but on the processing of non-prototypes in the L2 tense-aspect marking. This study extends previous research, showing the interaction effect of lexical aspect and grammatical aspect in the form-meaning association in L2 tense-aspect sentence processing.